Fractional-N PLL Synthesizer for FMCW Signal Generator with Dual-Mode Modulation Pattern - R. Indrawijaya; R. Sariningrum; B. Edi Sukoco; D. Muliawandana (Jurnal Elektronika dan Telekomunikasi, 2018)
Radar signal generator is a critical component in radar system as it determines the best achievable resolution. Single chip Fractional-N PLL synthesizer with built-in VCO and sweep modulator become more popular as Frequency Modulated Continuous Wave (FMCW) signal generator due to the simplicity and overall cost reduction. This paper presents a realization process and experimental result of dual-mode modulation pattern FMCW signal generator using HMC769LP6CE PLL. The PLL is controlled by ATMega328 microcontroller and Altera EPM240T100C5 CPLD to operate in two difference mode: 1-way sweep mode and 2-way sweep mode. The PLL is programmed with four different sweep bandwidth from 6.75–54 MHz for different range and resolution radar purpose. The performance of FMCW signal generator is measured using the output of passband signal spectrum. The experimental results indicate that the PLL-VCO with 2-way sweep mode has clearer frequency passband compared to 1-way sweep mode.